The Dow Doesn’t Serve Society - Bechtel, Gordon (Advances in Social Sciences Research Journal, 2021)
It has recently been shown that American GDP causes several human imperatives and is itself caused by globalization (Bechtel, 2021). This note reports a surprising exception to this finding; namely, in contrast to other human imperatives, the Dow doesn’t cause any good, nor is it caused by any good. The findings here will inform the conceptual collision between Federal Reserve theory and modern monetary theory (Kelton, 2021) vis-à-vis the global isolation of the Dow. Hopefully, this information will also prevent young holders, who can’t afford the long-term Dow strategy advocated by media pundits, from getting hurt.